2011
DOI: 10.5124/jkma.2011.54.11.1199
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up study on mortality in Korean stroke patients

Abstract: Stroke is the most common cause of death as single-diseases in South Korea. And it generates additional medical cost through high incidence of related disabilities and complications, which would become more important with the rapid aging process in Korean society. This study was preformed to identify stroke patients' mortality and its associated factors. Patients diagnosed as stroke (ICD-10 code I60-I63) in 2003 were identified. Their follow-up mortality rate in 5 years and related factors (stroke type, sex, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…If the keywords 'b' and 'f' are presented in paper C, the co-occurrence combination 'bf' is generated. In this case, 'f' is only linked to 'b', and 'b' serves as a mediator between 'f' and other keywords (a, c, d, and e) [12]. Repeating this process for the entire range of keywords in the present study produces the matrix data.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…If the keywords 'b' and 'f' are presented in paper C, the co-occurrence combination 'bf' is generated. In this case, 'f' is only linked to 'b', and 'b' serves as a mediator between 'f' and other keywords (a, c, d, and e) [12]. Repeating this process for the entire range of keywords in the present study produces the matrix data.…”
Section: Methodsmentioning
confidence: 98%
“…It can be concluded that health literacy research is the mainstream in developing education programs for patients and adults and measuring their effectiveness. These results might be due to a number of functional and practical studies aimed at achieving results such as resolving health inequality [11] and reduced hospitalization and emergency room use [12].…”
Section: Figure 5 Network Structure Of Subgroup 3: Apply and Use Of Vmentioning
confidence: 99%
“…It is clear that the incidence of cerebral hemorrhage among stroke patients in the general population has markedly decreased [5][6][7]. Great advances in brain image studies have contributed to the detection of developing infarctions.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Patients with acute ischaemic stroke (AIS) require continuous attention after stroke onset, especially within the first year, because it is associated with high mortality and recurrence rates within 1 year. A previous study reported that the mortality rate of patients with AIS was approximately 10% within 30 days and 20% within 1 year 2. In particular, deaths of vascular origin after AIS occur at a high rate, indicating the need for major adverse cerebro/cardiovascular event (MACE) risk prediction 3–5.…”
Section: Introductionmentioning
confidence: 99%